Use of molecular imprinted polymer for isolation of secondary metabolites in plants for drug raw material independence - Gunawan, Untung; Prasetyanto, Eko Adi; Falena, Pretty; Irlianto, Kellie; Ivansyah, Atthar Luqman (Institute of Computer Science (IOCS), 2025)
Indonesia, with its rich biodiversity, has numerous plant species with significant therapeutic potential. Secondary metabolites in plants play a vital role in pharmaceuticals, agriculture, and the food industry. However, traditional methods for isolating these compounds are often non-selective, time-consuming, and environmentally unfriendly. Molecularly Imprinted Polymer (MIP) is an emerging method for isolating secondary metabolites due to its selectivity and efficiency. MIP has been successfully applied in the identification and separation of plant-derived compounds, including secondary metabolites, chemical residues, and pesticides. This study explores the use of MIP for isolating secondary metabolites in plants and aims to contribute to developing strategies for obtaining targeted metabolites. The findings also highlight future research opportunities for MIP in industrial applications to support the independence of medicinal raw materials in Indonesia.